Coated catalyst for preparing lactone through diol dehydrocyclization, preparation method and application

By using a clad catalyst in the diol dehydrocyclization catalyst, the porous inert porcelain ball core and a clad layer containing copper, silicon, aluminum, cesium and chromium, the problems of high non-ferrous metal usage and by-product generation in the existing catalyst are solved, and the effects of cost reduction, increased lactone yield and extended catalyst life are achieved.

CN119588371AActive Publication Date: 2025-03-11WANHUA CHEM GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411615829.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-11
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The amount of non-ferrous metals used in existing diol dehydrocyclization catalysts is high, resulting in high production costs. At the same time, the generation of by-products affects the lactone yield and catalyst operating life.

Method used

The coating catalyst is used, and the core is a porous inert porcelain ball. The coating layer contains copper, silicon, aluminum, cesium and chromium. Through the rolling ball forming and high-temperature roasting process, a tightly bonded coating layer is formed, which significantly reduces the use of non-ferrous metals.

Benefits of technology

This significantly reduces the production cost of the catalyst, increases the lactone yield, extends the operating life of the catalyst, and reduces the generation of by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a coated lactone catalyst prepared through diol dehydrocyclization, a preparation method and application, aluminum oxide in a surface coating layer interacts with an inner core ceramic ball in the roasting process of the catalyst, and the compressive strength of the catalyst is high; a strong-basicity auxiliary agent cesium and a dehydrogenation auxiliary agent chromium are introduced, so that the side reactions of hydrogenolysis and dehydration are few, and the dehydrogenation selectivity is high. The catalyst provided by the invention greatly reduces the use amount of non-ferrous metals, significantly reduces the raw material cost of the catalyst, and is low in abrasion, small in dust and less in breakage in the production, transportation and filling processes. The catalyst disclosed by the invention is especially suitable for near-normal-pressure reaction working conditions due to uniform gaps after being filled and few support bridges and broken particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coated diol dehydrogenation cyclization catalyst for preparing lactone, a preparation method and application thereof, and belongs to the technical field of chemical catalysis. Background Art

[0002] The dehydrogenation and cyclization of diols to prepare lactones, such as the dehydrogenation of 1,4-butanediol to prepare γ-butyrolactone, the dehydrogenation of 1,5-pentanediol to prepare δ-valerolactone, the dehydrogenation of 1,6-hexanediol to prepare ε-caprolactone, and the dehydrogenation of diethylene glycol to prepare p-dioxanone, is a reaction pathway with high economic value. The lactone products obtained are widely used in solvents, organic synthesis intermediates, biodegradable materials and other fields.

[0003] The diol dehydrogenation cyclization reaction generally needs to be carried out under high temperature, near normal pressure or pressurized, and hydrogen conditions, and requires the assistance of a catalyst to reduce the reaction energy barrier, increase the reaction rate, and achieve a higher lactone yield (≥90%). At present, the commonly used catalyst system is mainly copper-based, such as Cu-Zn-Cr-Zr (CN1054843A), Cr-Cr-Mn-Ba (CN1081948A), Cu-Zn-Al, etc. The non-ferrous metal content in the catalyst is high, generally reaching 30-50%, and is mostly formed by tableting. Many metal species are embedded in the catalyst, becoming invalid sites that cannot be fully utilized, and causing the catalyst production cost to remain high. In the context of increasingly fierce competition in industries such as γ-butyrolactone, manufacturers have an urgent need to reduce production costs and improve product competitiveness. How to reduce the amount of non-ferrous metals used in diol dehydrogenation cyclization catalysts and improve catalytic effects has become a hot topic in industry research.

[0004] The dehydrogenation cyclization reaction of diols is often accompanied by the formation of by-products. For example, when 1,4-butanediol is dehydrogenated to produce γ-butyrolactone, light components such as dihydrofuran, tetrahydrofuran, n-butanol, 2-hydroxytetrahydrofuran, etc. may also be generated, and heavy components such as various C8 acetals such as 2-(4-hydroxybutoxy)tetrahydrofuran, various C8 esters such as butyl butyrate, and even heavier components are generated. Among them, tetrahydrofuran is the dehydration product of 1,4-butanediol or the dehydrogenation product of n-butanol, n-butanol is the hydrogenolysis product of 1,4-butanediol, and 2-(4-hydroxybutoxy)tetrahydrofuran is the dehydrogenation intermediate and the product of the polycondensation of 1,4-butanediol raw materials. When the residence time of 1,4-butanediol on the catalyst surface is too long, a large number of side reactions such as dehydration, hydrogenolysis, and polycondensation occur, which will cause a decrease in the yield of γ-butyrolactone.

[0005] In addition, when the reaction temperature is too low, the rate at which intermediate products of the dehydrogenation reaction of 1,4-butanediol, such as 2-hydroxytetrahydrofuran, are further converted into γ-butyrolactone slows down, and 2-hydroxytetrahydrofuran and 1,4-butanediol react to generate a large amount of hemiacetal and acetal species such as 2-(4-hydroxybutoxy)tetrahydrofuran, which not only reduces the yield of the main product of γ-butyrolactone, but also covers the active sites of the catalyst, affecting the operating life of the catalyst.

[0006] With the scale and size of the reaction unit, the diameter and length of the tubes of the dehydrogenation reactor have shown an obvious increasing trend. However, the heat transfer capacity of the existing catalyst is limited, and the cold spot temperature inside the reaction tube is too low. The above-mentioned heavy byproducts will be generated in large quantities and discharged from the bottom of the subsequent de-heavy distillation tower together with the unreacted 1,4-butanediol. 1,4-Butanediol and 2-(4-hydroxybutoxy)tetrahydrofuran have similar boiling points and are difficult to separate. The bottom liquid cannot be used efficiently and can only be incinerated, causing economic losses. Summary of the invention

[0007] In order to solve the above-mentioned industry pain points, the present invention provides a catalyst for preparing lactone by dehydrogenation cyclization of diols.

[0008] The technical solution of the present invention is as follows:

[0009] A catalyst for preparing lactone by dehydrogenation and cyclization of diols, the catalyst being of coated type, comprising an inner core and a coating layer; the inner core is a porous inert porcelain ball, and the coating layer is a mixture containing copper, silicon, aluminum, cesium and chromium elements;

[0010] The porous inert ceramic ball is a mixture of inert alumina and silicon oxide or inert alumina. In the inner core porous inert ceramic ball, the mass ratio of silicon oxide to alumina is 0 to 1, for example, 0 (pure alumina in this case), 0.3, 0.6, 0.8, 1, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0011] The diameter of the porous inert ceramic ball of the inner core is 2 to 5 mm, for example, it can be 2 mm, 3 mm, 4 mm, 5 mm, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable;

[0012] Preferably, based on the mass of the inner core, the water absorption rate of the inner core porous inert porcelain ball is 5-20%, for example, it can be 5%, 10%, 15%, 20%, etc., but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0013] Preferably, the thermal conductivity of the inner core porous inert ceramic ball is 10 to 30 W / (m·K), for example, it can be 10 W / (m·K), 17 W / (m·K), 24 W / (m·K), 30 W / (m·K), etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] The copper, silicon, aluminum, cesium and chromium elements of the coating layer exist in an oxidized form, for example, copper oxide, silicon oxide, aluminum oxide, cesium oxide, silicate, metaaluminate, chromium oxide, chromate, dichromate or a composite oxide or compound composed of two or more of the above elements;

[0015] Preferably, the coating layer has a thickness of 0.5 to 3 mm, for example, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 3 mm, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0016] As an embodiment, the coating layer of the catalyst comprises, based on the coating layer, 4 to 20 wt% of copper oxide, 4 to 20 wt% of silicon oxide, 0.05 to 5 wt% of cesium oxide, 0.4 to 10 wt% of chromium oxide (calculated as chromium trioxide) and 45 to 91.55 wt% of aluminum oxide;

[0017] More preferably, it comprises 5-15wt% of copper oxide, 5-15wt% of silicon oxide, 0.1-3% of cesium oxide, 0.5-3% of chromium trioxide and 64-89.4% of aluminum oxide;

[0018] Preferably, based on the coating layer, the copper oxide content is 5 to 15 wt%, for example, 5 wt%, 8 wt%, 11 wt%, 13 wt%, 15 wt%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0019] Preferably, based on the coating layer, the silicon oxide content is 5 to 15 wt%, for example, 5 wt%, 8 wt%, 11 wt%, 13 wt%, 15 wt%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0020] Preferably, based on the coating layer, the cesium oxide content is 0.1 to 3 wt%, for example, 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0021] Preferably, based on the coating layer, the chromium oxide (calculated as chromium trioxide) content is 0.5-3wt%, for example, 0.5wt%, 1.0wt%, 1.7wt%, 2.4wt%, 3wt%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0022] Preferably, based on the coating layer, the aluminum oxide content is 64 to 89.4 wt%, for example, 64 wt%, 70 wt%, 76 wt%, 82 wt%, 89.5 wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] The active species of this type of catalyst are evenly distributed in the outer layer of the catalyst, which greatly reduces the use of non-ferrous metals and significantly reduces the production cost of the catalyst. More importantly, it avoids the disadvantage of diols diffusing into the interior of the catalyst and causing a long residence time, thereby reducing the possibility of side reactions such as hydrogenolysis, dehydration, and polycondensation of the raw material molecules at the active sites of the catalyst, and can improve the lactone yield. In addition, the dehydrogenation reaction is a strong endothermic reaction, and the inert ceramic ball core with high thermal conductivity can realize the rapid supply of external heat, avoiding the cold spot temperature of the catalyst bed inside the reaction tube from being too low, thereby further inhibiting the generation of high-boiling species such as hemiacetal and acetal, and further improving the operating life of the catalyst. In some application examples, the catalyst has been running stably for 8000h without reducing the catalytic effect.

[0024] The present invention also provides a method for preparing a diol dehydrogenation catalyst, which mainly comprises the following steps:

[0025] (1) adding a copper source, a cesium source, a chromium source or a solution thereof into ammonia water to dissolve and disperse to obtain a mixed solution X;

[0026] (2) adding a silicon source and an aluminum source to the mixed solution X, and then heating and evaporating ammonia to obtain a precursor;

[0027] (3) mixing the precursor and the binder aqueous solution and coating the core;

[0028] (4) Drying and calcining the coated product to obtain a finished coated catalyst.

[0029] In step (1), the copper source may be one or more of copper nitrate, copper carbonate, basic copper carbonate, copper hydroxide, copper formate, copper acetate, copper oxalate, copper citrate, copper oxide, cuprous oxide, and copper powder.

[0030] The cesium source may be one or more of cesium nitrate, cesium carbonate, cesium hydroxide, cesium formate, cesium acetate, cesium oxalate, cesium citrate, and cesium oxide.

[0031] The chromium source may be one or more of chromium nitrate, chromium carbonate, chromium hydroxide, chromium formate, chromium acetate, chromium oxalate, chromium citrate, chromium trioxide, chromium dioxide, chromium trioxide, chromate, and dichromate.

[0032] The concentration of the aqueous ammonia is 10-50wt%, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] There is no restriction on the order of adding the copper source, cesium source, chromium source or their solutions into the ammonia water, and the solution is an aqueous solution.

[0034] The dissolution and dispersion temperature is 10-60°C, for example, 10°C, 25°C, 40°C, 50°C, 60°C, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] The dissolution and dispersion operation is carried out during stirring, the stirring speed is not limited, and the dissolution and dispersion time is unlimited, and finally a mixed solution X is obtained, in which the components of the liquid or slurry are uniformly mixed and distributed.

[0036] In step (2), the silicon source may be one or more of silicon dioxide, silica sol, silica-alumina sol, tetramethyl silicate, and tetraethyl silicate.

[0037] The aluminum source can be one or more of aluminum nitrate, aluminum carbonate, aluminum hydroxide, aluminic acid, aluminate, aluminum formate, aluminum acetate, aluminum oxalate, aluminum citrate, aluminum alcohols, alkyl aluminums, hydrated aluminum oxide, aluminum oxide, aluminum powder, silica-alumina sol, and aluminum sol.

[0038] There is no restriction on the order of adding the silicon source and the aluminum source. The silicon source and the aluminum source can be added as pure substances or as aqueous solutions and added to the mixed solution X.

[0039] The heating rate of the ammonia evaporation operation is 10 to 60°C / h, for example, 10°C / h, 20°C / h, 35°C / h, 50°C / h, 60°C / h, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] The temperature end point of the ammonia evaporation operation is 85-99°C, for example, 85°C, 88°C, 91°C, 95°C, 99°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The ammonia evaporation operation is carried out during stirring, and the stirring speed is unlimited, and the time of the ammonia evaporation operation is unlimited. The precursor finally obtained is a powder, and each component of the powder is in a state of uniform mixing and distribution.

[0042] In step (3), the binder may be one or more of water, silica sol, silica-alumina sol, aluminum sol, polyethylene glycol, polyvinyl alcohol, cellulose, guar gum, sesbania powder, gum arabic powder, starch, nitric acid, glycerin, and corn dextrin.

[0043] The mass ratio of the amount of binder added to the amount of precursor used is 0.01 to 0.1, for example, it can be 0.01, 0.03, 0.05, 0.08, 0.1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] The precursor and the binder are mixed in a mixer or a grinder using conventional industry operating methods, and ultimately the precursor and the binder aqueous solution are evenly dispersed to obtain a viscous powder or slurry.

[0045] The method of coating the inner core is a ball rolling method, which can be performed by using conventional industry methods. A constant temperature and humidity environment is preferred to ensure that the quality of the ball is more uniform.

[0046] In step (4), the drying operation is generally carried out in an oven or a belt desiccant, and other drying equipment commonly used in other industries can also be used without special restrictions.

[0047] The temperature of the drying operation is 80-180°C, for example, 80°C, 100°C, 120°C, 150°C, 180°C, etc., but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable. The specific drying temperature should ensure that a large amount of water evaporates from the spheres during the drying process but no obvious migration and redistribution of active components occurs.

[0048] The roasting operation is generally carried out in a muffle furnace, a rotary kiln or a pusher kiln, and other common roasting equipment in other industries can also be used without special restrictions.

[0049] The temperature of the calcination operation is 200-650°C, for example 200°C, 300°C, 400°C, 520°C, 650°C, etc., but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable. The specific calcination temperature should ensure that the carbon and nitrogen impurities in the catalyst are decomposed and escape from the catalyst.

[0050] The present invention also provides application of the catalyst in preparing lactone by dehydrogenation cyclization of diol compounds.

[0051] Preferably, the diol compound is any one of 1,3-propylene glycol, 1,4-butanediol, 1,4-pentanediol, 1,5-pentanediol, 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol or diethylene glycol and their derivatives, or a combination of at least two thereof.

[0052] More preferably, the diol compound is any one of 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol or diethylene glycol and derivatives thereof, or a combination of at least two thereof.

[0053] More preferably, at least one hydrogen atom attached to carbon in the derivative is substituted by an alkyl group, an ether bond, a hydroxyl group, a carbonyl group, a carboxyl group, an ester group, an amino group, an imino group, a nitro group, a nitroso group, a cyano group, an amide group or an aromatic group.

[0054] In the application of the present invention, the process of the dehydrogenation reaction is: the diol compound is mixed with hydrogen and vaporized, and then dehydrogenated and cyclized to generate the corresponding lactone.

[0055] The catalyst also needs to be reduced before the dehydrogenation reaction. There is no special restriction on the reduction conditions. The reduction is an exothermic reaction process, and the reduction temperature rise is required to be less than 20°C to avoid catalyst sintering. After reduction, the copper species in the catalyst exists in the form of copper alone.

[0056] Preferably, the temperature of the dehydrogenation reaction is 180-350°C, for example, 180°C, 230°C, 280°C, 310°C, 350°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The specific temperature setting value should ensure that the diol and hydrogen are in a gas phase state in the reactor after being mixed and fed.

[0057] Preferably, the volume space velocity of the diol raw material for the dehydrogenation reaction is 0.01 to 2 h -1 , for example, it can be 0.01h -1 , 0.05h -1 , 0.1h -1 , 1h -1 , 2h -1 The above range is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0058] Preferably, the dehydrogenation reaction is a hydrogenation reaction, and the molar ratio of hydrogen to alcohol is (1-30):1, for example, 1:1, 5:1, 10:1, 20:1, 30:1, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] Preferably, the pressure of the dehydrogenation reaction is 0.01-1 MPaG, for example, 0.01 MPaG, 0.1 MPaG, 0.3 MPaG, 0.5 MPaG, 1 MPaG, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] The beneficial effects of the present invention are:

[0061] The coated catalyst prepared by the present invention greatly reduces the amount of non-ferrous metals used and can significantly reduce the cost of catalyst raw materials. In some application examples, the production cost of the coated catalyst prepared by the rolling ball molding of the present invention is reduced by more than 50% compared with the production cost of the traditional cylindrical molding catalyst.

[0062] Due to the presence of the inert ceramic ball inner core of the catalyst of the present invention, the compressive strength of the catalyst is greatly improved. The alumina in the surface coating layer interacts with the alumina in the inner ceramic ball during the catalyst roasting process, so that the coating layer is tightly combined with the inner core. In some application examples, the allowable catalyst loading height is greater than 10m, and the catalyst does not crack or break.

[0063] Both the dehydration side reaction and the hydrogenolysis side reaction require the catalytic action of acidic active sites. The introduction of alumina into the catalyst improves the binding ability between the coating layer and the core, while introducing acidic sites. In order to eliminate its adverse effects, the strong alkaline auxiliary agent cesium is introduced into the catalyst. The introduction of cesium strongly inhibits the dehydration side reaction and improves the selectivity of the main dehydrogenation product lactone. The dehydrogenation auxiliary agent chromium is also introduced into the catalyst. Chromium and copper work synergistically to strongly inhibit the hydrogenolysis side reaction and further improve the dehydrogenation selectivity.

[0064] Under the same composition, the coated catalyst obtained by the rolling ball molding of the present invention has the advantages of low wear, less dust and less breakage during production, transportation and loading, compared with the traditional cylindrical molding catalyst, and is more friendly to loading workers and the environment. The catalyst of the present invention is particularly suitable for near-normal pressure reaction conditions because of uniform gaps after loading, less bridging and broken particles. In some application examples of 1,4-butanediol dehydrogenation to prepare γ-butyrolactone, the inner diameter of the reaction tube is 50mm, the catalyst loading height is 5m, and the volume space velocity is 0.12h -1 , hydrogen-alcohol ratio of 13, reaction pressure 101kPaG, reaction temperature 240°C, the measured bed pressure drop was only 7kPa, and the bed cold point was only 228°C. DETAILED DESCRIPTION

[0065] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0066] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the related listed items. The top, bottom, etc. mentioned or may be mentioned in this specification are defined relative to the structure. They are relative concepts and may therefore change accordingly according to their different locations and different usage states.

[0067] Main raw material sources

[0068] Basic copper carbonate, copper nitrate trihydrate, copper hydroxide, copper acetate, cesium carbonate, cesium nitrate, cesium hydroxide, cesium acetate, ammonium chromate, chromium nitrate nonahydrate, chromium trioxide, chromium acetate, ammonia, tetraethyl silicate, gas phase SiO2, aluminum nitrate nonahydrate, aluminum hydroxide, sesbania powder, guar gum, and nitric acid were purchased from Aladdin Reagent (Shanghai) Co., Ltd. Silica sol was purchased from Shandong Kehan ​​Silicon Products Co., Ltd., aluminum sol was purchased from Suzhou Baird New Materials Technology Co., Ltd., pseudo-boehmite was purchased from Shandong Yuneng Technology Co., Ltd., porcelain balls were purchased from Jiangxi Anfa Environmental Protection New Materials Co., Ltd., hydrogen was purchased from Air Liquide, and 1,4-butanediol was sourced from Wanhua Chemical.

[0069] Analytical methods:

[0070] The product composition was analyzed by gas chromatography and the diol conversion rate and selectivity were calculated by the area method: instrument model: Agilent 8890; chromatographic column: HP-Innowax (30m×0.25mm×0.25μm); injection volume 0.5μL, vaporization chamber temperature 220℃; column box initial temperature 50℃, starting waiting time 2min, then increased to 80℃ at a rate of 5℃ / min, and then increased to 260℃ at a rate of 15℃ / min, and maintained for 10min; the carrier gas was high-purity nitrogen, with a split ratio of 30:1 and a split flow rate of 30mL / min; the detector was an ion flame detector, temperature 260℃, air flow rate 400mL / min, hydrogen flow rate 30mL / min, and tail gas flow rate 25mL / min.

[0071] Example

[0072] Example 1

[0073] (1) 12.15 g of copper nitrate trihydrate, 0.07 g of cesium nitrate, and 1.60 g of chromium nitrate nonahydrate were added to 60 g of 50% ammonia water to dissolve and disperse to obtain a mixed solution X1 at a dissolution and dispersion temperature of 25° C.;

[0074] (2) adding 20.00 g of 20% silica sol and 305.17 g of 30% aluminum sol to the mixed solution X1, and then heating to 85°C at 10°C / h to evaporate ammonia to obtain precursor Z1;

[0075] (3) 100 g of precursor Z1 was mixed with a binder guar gum solution, with the amount of guar gum being 5 g, to obtain a sticky solid powder; the powder was then rolled onto an alumina ceramic ball core with a diameter of 2 mm, a thermal conductivity of 28 W / (m·K), and a water absorption rate of 5%, with a coating layer thickness of ∼3 mm;

[0076] (4) The coated product is dried at 180°C and then calcined at 650°C to obtain a finished coated catalyst.

[0077] The composition of the catalyst coating layer prepared in this example is 4% CuO-4% SiO2-0.05% Cs2O-0.4% CrO3-91.55% Al2O3.

[0078] Example 2

[0079] (1) 60.74 g of copper nitrate trihydrate, 6.92 g of cesium nitrate, and 40.02 g of chromium nitrate nonahydrate were added to 370 g of 50% ammonia water to dissolve and disperse to obtain a mixed solution X2 at a dissolution and dispersion temperature of 25° C.;

[0080] (2) adding 100.00 g of 20% silica sol and 150.00 g of 30% aluminum sol to the mixed solution X2, and then heating to 95° C. at 60° C. / h to evaporate ammonia to obtain precursor Z2;

[0081] (3) 100 g of precursor Z2 was taken and mixed with a binder guar gum solution, with the amount of guar gum being 5 g, to obtain a sticky solid powder; the powder was then rolled and coated on an alumina ceramic ball core with a diameter of 5 mm, a thermal conductivity of 30 W / (m·K), and a water absorption rate of 5%, with a coating layer thickness of ∼0.5 mm;

[0082] (4) The coated product is dried at 80°C and then calcined at 650°C to obtain a finished coated catalyst.

[0083] The composition of the catalyst coating layer prepared in this embodiment is 20% CuO-20% SiO2-5% Cs2O-10% CrO3-45% Al2O3.

[0084] Example 3

[0085] (1) 7.13 g of basic copper carbonate, 0.12 g of cesium carbonate, and 0.76 g of ammonium chromate were added to 840 g of 20% ammonia water and dissolved and dispersed to obtain a mixed solution X3 at a dissolution and dispersion temperature of 10° C.;

[0086] (2) adding 15.00 g of gaseous SiO2 and 584.26 g of aluminum nitrate nonahydrate to the mixed solution X3, and then heating to 90°C at 25°C / h to evaporate ammonia to obtain the precursor Z3;

[0087] (3) 100 g of precursor Z3 was mixed with a 3% nitric acid solution of pseudo-boehmite as a binder, with the pseudo-boehmite used in an amount of 10 g, to obtain a sticky solid powder; the powder was then rolled onto a silicon oxide alumina ceramic ball core with a diameter of 3 mm, a thermal conductivity of 18 W / (m·K), and a water absorption rate of 16%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.06, and the coating layer thickness was 2 mm;

[0088] (4) The coated product was dried at 120°C and then calcined at 550°C to obtain a finished coated catalyst.

[0089] The composition of the catalyst coating layer prepared in this embodiment is 5% CuO-15% SiO2-0.1% Cs2O-0.5% CrO3-79.4% Al2O3.

[0090] Example 4

[0091] (1) 21.40 g of basic copper carbonate, 1.16 g of cesium carbonate, and 2.28 g of ammonium chromate were added to 850 g of 20% ammonia water and dissolved and dispersed to obtain a mixed solution X4 at a dissolution and dispersion temperature of 10° C.;

[0092] (2) adding 10.00 g of gaseous SiO2 and 533.48 g of aluminum nitrate nonahydrate to the mixed solution X4, and then heating to 90°C at 25°C / h to evaporate ammonia to obtain the precursor Z4;

[0093] (3) 100 g of precursor Z4 was mixed with a 3% nitric acid solution of pseudo-boehmite as a binder, with the pseudo-boehmite used in an amount of 10 g, to obtain a sticky solid powder; the powder was then rolled onto a silicon oxide alumina ceramic ball core with a diameter of 3 mm, a thermal conductivity of 18 W / (m·K), and a water absorption rate of 16%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.06, and the coating layer thickness was 2 mm;

[0094] (4) The coated product was dried at 120°C and then calcined at 550°C to obtain a finished coated catalyst.

[0095] The composition of the catalyst coating layer prepared in this embodiment is 15% CuO-10% SiO2-1% Cs2O-1.5% CrO3-72.5% Al2O3.

[0096] Example 5

[0097] (1) 14.26 g of basic copper carbonate, 3.47 g of cesium carbonate, and 4.56 g of ammonium chromate were added to 880 g of 20% aqueous ammonia and dissolved to obtain a mixed solution X5 at a dissolution and dispersion temperature of 10° C.;

[0098] (2) adding 5.00 g of gaseous SiO2 and 581.31 g of aluminum nitrate nonahydrate to the mixed solution X5, and then heating to 90°C at 25°C / h to evaporate ammonia to obtain the precursor Z5;

[0099] (3) 100 g of precursor Z5 was mixed with a 3% nitric acid solution of pseudo-boehmite as a binder, with the pseudo-boehmite used in an amount of 10 g, to obtain a sticky solid powder; the powder was then rolled onto a silicon oxide alumina ceramic ball core with a diameter of 3 mm, a thermal conductivity of 18 W / (m·K), and a water absorption rate of 16%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.06, and the coating layer thickness was 2 mm;

[0100] (4) The coated product was dried at 120°C and then calcined at 550°C to obtain a finished coated catalyst.

[0101] The composition of the catalyst coating layer prepared in this embodiment is 10% CuO-5% SiO2-3% Cs2O-3% CrO3-79% Al2O3.

[0102] Example 6

[0103] (1) 18.40 g of copper hydroxide, 1.06 g of cesium hydroxide and 1.50 g of chromium trioxide were added to 610 g of 28% ammonia water and dissolved and dispersed to obtain a mixed solution X6 at a dissolution and dispersion temperature of 50° C.;

[0104] (2) adding 34.68 g of tetraethyl silicate and 110.93 g of aluminum hydroxide to the mixed solution X6, and then heating to 92° C. at 60° C. / h to evaporate ammonia to obtain the precursor Z6;

[0105] (3) 100 g of precursor Z6 was mixed with a 5% nitric acid solution as a binder, with 1 g of nitric acid used, to obtain a sticky solid powder; the powder was then rolled onto a silicon oxide aluminum ceramic ball core with a diameter of 4 mm, a thermal conductivity of 25 W / (m·K), and a water absorption rate of 9%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.03, and the coating layer thickness was ∼1.5 mm;

[0106] (4) The coated product is dried at 100°C and then calcined at 600°C to obtain a finished coated catalyst.

[0107] The composition of the catalyst coating layer prepared in this embodiment is 15% CuO-10% SiO2-1% Cs2O-1.5% CrO3-72.5% Al2O3.

[0108] Example 7

[0109] (1) 34.25 g of copper acetate, 1.36 g of cesium acetate and 3.44 g of chromium acetate were added to 610 g of 28% ammonia water to dissolve and disperse to obtain a mixed solution X7 at a dissolution and dispersion temperature of 50° C.;

[0110] (2) adding 34.68 g of tetraethyl silicate and 110.93 g of aluminum hydroxide to the mixed solution X7, and then heating to 92° C. at 20° C. / h to evaporate ammonia to obtain the precursor Z7;

[0111] (3) 100 g of precursor Z7 was mixed with a 5% nitric acid solution as a binder, with 1 g of nitric acid used, to obtain a sticky solid powder; the powder was then rolled onto a silicon-aluminum ceramic ball core with a diameter of 4 mm, a thermal conductivity of 10 W / (m·K), and a water absorption of 17%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.08, and the coating thickness was ∼1.5 mm;

[0112] (4) The coated product is dried at 100°C and then calcined at 600°C to obtain a finished coated catalyst.

[0113] The composition of the catalyst coating layer prepared in this embodiment is 15% CuO-10% SiO2-1% Cs2O-1.5% CrO3-72.5% Al2O3.

[0114] Example 8

[0115] (1) 34.25 g of copper acetate, 1.16 g of cesium carbonate, and 1.50 g of chromium trioxide were added to 1300 g of 10% ammonia water to dissolve and disperse to obtain a mixed solution X8 at a dissolution and dispersion temperature of 60° C.;

[0116] (2) adding 50.00 g of 20% silica sol and 110.93 g of aluminum hydroxide to the mixed solution X8, and then heating to 92° C. at 40° C. / h to evaporate ammonia to obtain the precursor Z8;

[0117] (3) 100 g of precursor Z8 was taken and mixed with a binder, sesbania powder, and 20% silica sol, with the amount of sesbania powder used being 2.00 g and the amount of SiO2 used being 3.00 g, to obtain a sticky solid powder; the powder was then rolled and coated on a silicon-alumina ceramic ball core with a diameter of 4 mm, a thermal conductivity of 12 W / (m·K), and a water absorption rate of 20%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.10, and the coating layer thickness was ∼1.5 mm;

[0118] (4) The coated product is dried at 150°C and then calcined at 200°C to obtain a finished coated catalyst.

[0119] The composition of the catalyst coating layer prepared in this embodiment is 15% CuO-10% SiO2-1% Cs2O-1.5% CrO3-72.5% Al2O3.

[0120] Comparative Example

[0121] Comparative Example 1

[0122] (1) 21.40 g of basic copper carbonate, 1.16 g of cesium carbonate, and 2.28 g of ammonium chromate were added to 950 g of 20% aqueous ammonia and dissolved to obtain a mixed solution X9 at a dissolution and dispersion temperature of 10° C.;

[0123] (2) adding 607.07 g of aluminum nitrate nonahydrate to the mixed solution X9, and then heating the solution to 90° C. at 25° C. / h to evaporate ammonia to obtain a precursor Z9;

[0124] (3) 100 g of precursor Z9 was mixed with a 3% nitric acid solution of pseudo-boehmite as a binder, with the pseudo-boehmite used in an amount of 10 g, to obtain a sticky solid powder; the powder was then rolled onto a silicon-aluminum ceramic ball core with a diameter of 3 mm, a thermal conductivity of 18 W / (m·K), and a water absorption rate of 16%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.06, and the coating layer thickness was 2 mm;

[0125] (4) The coated product was dried at 120°C and then calcined at 550°C to obtain a finished coated catalyst.

[0126] The catalyst coating layer prepared in this comparative example does not contain silicon, and the composition of the catalyst coating layer is 15% CuO-1% Cs2O-1.5% CrO3-82.5% Al2O3.

[0127] Comparative Example 2

[0128] (1) 21.40 g of basic copper carbonate and 2.28 g of ammonium chromate were added to 860 g of 20% aqueous ammonia and dissolved to obtain a mixed solution X10 at a dissolution and dispersion temperature of 10° C.;

[0129] (2) adding 10.00 g of gaseous SiO2 and 540.84 g of aluminum nitrate nonahydrate to the mixed solution X10, and then heating to 90°C at 25°C / h to evaporate ammonia to obtain the precursor Z9;

[0130] (3) 100 g of precursor Z10 was mixed with a 3% nitric acid solution of pseudo-boehmite as a binder, with the pseudo-boehmite used in an amount of 10 g, to obtain a sticky solid powder; the powder was then rolled onto a silicon-aluminum ceramic ball core with a diameter of 3 mm, a thermal conductivity of 18 W / (m·K), and a water absorption rate of 16%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.06, and the coating layer thickness was 2 mm;

[0131] (4) The coated product was dried at 120°C and then calcined at 550°C to obtain a finished coated catalyst.

[0132] The catalyst coating layer prepared in this comparative example does not contain cesium, and the composition of the catalyst coating layer is 15% CuO-10% SiO2-1.5% CrO3-73.5% Al2O3.

[0133] Comparative Example 3

[0134] (1) 21.40 g of basic copper carbonate and 1.16 g of cesium carbonate were added to 860 g of 20% aqueous ammonia and dissolved to obtain a mixed solution X11 at a dissolution and dispersion temperature of 10° C.;

[0135] (2) adding 10.00 g of gaseous SiO2 and 544.52 g of aluminum nitrate nonahydrate to the mixed solution X11, and then heating to 90°C at 25°C / h to evaporate ammonia to obtain the precursor Z10;

[0136] (3) 100 g of precursor Z11 was mixed with a 3% nitric acid solution of pseudo-boehmite as a binder, with the pseudo-boehmite used in an amount of 10 g, to obtain a sticky solid powder; the powder was then rolled onto a silicon-aluminum ceramic ball core with a diameter of 3 mm, a thermal conductivity of 18 W / (m·K), and a water absorption rate of 16%, wherein the mass ratio of silicon oxide to aluminum oxide in the core was 0.06, and the coating layer thickness was 2 mm;

[0137] (4) The coated product was dried at 120°C and then calcined at 550°C to obtain a finished coated catalyst.

[0138] The catalyst coating layer prepared in this comparative example does not contain chromium, and the composition of the catalyst coating layer is 15% CuO-10% SiO2-1% Cs2O-74% Al2O3.

[0139] Catalyst performance test:

[0140] Take 50g of the dehydrogenation catalyst prepared in the above examples and comparative examples, and load it into a stainless steel reaction tube with an inner diameter of 30mm and a length of 800cm in the middle. The reaction tube is filled with inert quartz sand fillers on the top and bottom. First, dry it at 160℃ for 2h under nitrogen atmosphere and pressure of 0.1MPaG; then switch to hydrogen atmosphere for reduction, gradually increase the hydrogen concentration from 0.5% to 100%, and gradually increase the bed temperature from 160℃ to 250℃. Observe the reduction exotherm and control the reduction temperature rise to less than 20℃. Start feeding after 48h of reduction.

[0141] Using 1,4-butanediol as the reaction substrate and a hydrogen / alcohol ratio of 10 (molar ratio), the results are shown in Table 1.

[0142] Table 1

[0143]

[0144]

[0145] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A dehydrogenation catalyst, characterized in that: The catalyst is of coated type, comprising a core and a coating layer; The inner core is a porous inert porcelain ball, and the coating layer is a mixture containing copper, silicon, aluminum, cesium and chromium elements; The coating layer of the catalyst comprises, based on the coating layer, 4-20 wt% of copper oxide, 4-20 wt% of silicon oxide, 0.05-5 wt% of cesium oxide, 0.4-10 wt% of chromium oxide (calculated as chromium trioxide) and 45-91.55 wt% of aluminum oxide, preferably, 5-15 wt% of copper oxide, 5-15 wt% of silicon oxide, 0.1-3% of cesium oxide, 0.5-3% of chromium trioxide and 64-89.4% of aluminum oxide; Preferably, the coating layer has a thickness of 0.5 to 3 mm.

2. The catalyst according to claim 1, characterized in that: The porous inert ceramic ball is a mixture of inert alumina and silicon oxide or inert alumina, and the mass ratio of silicon oxide to alumina is 0 to 1; Preferably, the diameter of the inner core porous inert porcelain ball is 2 to 5 mm; Preferably, based on the mass of the inner core, the water absorption rate of the inner core porous inert porcelain ball is 5-20%; Preferably, the thermal conductivity of the porous inert ceramic ball as the inner core is 10 to 30 W / (m·K).

3. A method for preparing the catalyst according to claim 1 or 2, comprising the following steps: (1) adding a copper source, a cesium source, a chromium source or a solution thereof into ammonia water to dissolve and disperse the source to obtain a mixed solution X; (2) adding a silicon source and an aluminum source to the mixed solution X, and then heating and evaporating ammonia to obtain a precursor; (3) mixing the precursor and the binder and coating the core; (4) Drying and calcining the coated product to obtain a finished coated catalyst.

4. The preparation method according to claim 3, characterized in that: In step (1), the copper source is one or more of copper nitrate, copper carbonate, basic copper carbonate, copper hydroxide, copper formate, copper acetate, copper oxalate, copper citrate, copper oxide, cuprous oxide, and copper powder; the cesium source is one or more of cesium nitrate, cesium carbonate, cesium hydroxide, cesium formate, cesium acetate, cesium oxalate, cesium citrate, and cesium oxide; and the chromium source is one or more of chromium nitrate, chromium carbonate, chromium hydroxide, chromium formate, chromium acetate, chromium oxalate, chromium citrate, chromium trioxide, chromium dioxide, chromium trioxide, chromate, and dichromate; The concentration of the aqueous ammonia is preferably 10 to 50 wt%; The dissolution and dispersion temperature is preferably 10 to 60°C.

5. The preparation method according to claim 3, characterized in that: In step (2), the silicon source is one or more of silicon dioxide, silica sol, silica-alumina sol, tetramethyl silicate, and tetraethyl silicate, and the aluminum source is one or more of aluminum nitrate, aluminum carbonate, aluminum hydroxide, aluminic acid, aluminates, aluminum formate, aluminum acetate, aluminum oxalate, aluminum citrate, aluminum alcohols, alkyl aluminums, hydrated aluminum oxide, aluminum oxide, aluminum powder, silica-alumina sol, and aluminum sol; The heating rate is preferably 10-60°C / h, and the final temperature of the heated ammonia evaporation is preferably 85-99°C.

6. The preparation method according to claim 3, characterized in that: In step (3), the binder is one or more of water, silica sol, silica-alumina sol, aluminum sol, polyethylene glycol, polyvinyl alcohol, cellulose, guar gum, sesbania powder, gum arabic powder, starch, nitric acid, glycerin, and corn dextrin; Preferably, the mass ratio of the amount of the binder added to the amount of the precursor used is 0.01 to 0.

1.

7. The preparation method according to claim 3, characterized in that: In step (4), the drying temperature is 80-180°C, and the calcination temperature is 200-650°C.

8. Use of the catalyst as claimed in claim 1 or 2 in the preparation of lactone by dehydrogenation cyclization of diol compounds.

9. The use according to claim 8, characterized in that: The diol compound includes any one or a combination of at least two of 1,3-propylene glycol, 1,4-butanediol, 1,4-pentanediol, 1,5-pentanediol, 1,4-hexanediol, 1,5-hexanediol, 1,6-hexanediol or diethylene glycol and their derivatives; Preferably, at least one hydrogen atom attached to carbon in the derivative is substituted by an alkyl group, an ether bond, a hydroxyl group, a carbonyl group, a carboxyl group, an ester group, an amino group, an imino group, a nitro group, a nitroso group, a cyano group, an amide group or an aromatic group.

10. The use according to claim 8 or 9, characterized in that: The diol compound is mixed with hydrogen and vaporized, and then dehydrogenated and cyclized to form the corresponding lactone; Preferably, the temperature of the dehydrogenation reaction is 180 to 350°C; Preferably, the volume space velocity of the dehydrogenation reaction is 0.01 to 2 h -1 ; Preferably, the dehydrogenation reaction is a hydrogenation reaction, and the molar ratio of hydrogen to alcohol is (1-30):1; Preferably, the pressure of the dehydrogenation reaction is 0.01-1 MPaG.

Citation Information

Patent Citations

  • Color image processing apparatus

    CN1054843A

  • Shaped abrasive particles and method of making same

    CN1081948A

  • Oxalate hydrogenation catalyst for producing ethanol and preparation method of catalyst

    CN105126845A

  • Dehydrogenation catalyst as well as preparation method and application thereof

    CN117654528A

  • Catalyst for liquid-phase dehydogenation of cyclohexanol

    CN1381435A